Analysis of mixed learning mode of distance education based on MOOC. (24th March 2022) - Li, Zhikai
In order to improve the evaluation ability of mixed learning in distance education, a mixed learning mode of distance education based on massive open online course (MOOC) is proposed. By building the distance education based on MOOC mixed study effect evaluation of heterogeneous storage structure of data model, remote education characteristics of distribution of blended learning model, remote education multi-parameter fusion model of blended learning and remote education blended learning process and effect evaluation of multi-parameter fusion model, multidimensional characteristics evaluation method is applied to the remote education blended learning model optimisation. The simulation results show that this method has better process control ability and higher reliability in learning effect evaluation, which effectively improves the mixed learning effect of MOOC-based distance education.